Pemberontakan VSTP di Semarang Tahun 1923 dan Potensi Pengembangan Bahan Pembelajaran Sejarahnya - Ismail, Akhmat Safiudin; Sulistyo, Wahyu Djoko (Jayapangus Press, 2024)
History is not only about studying the past, but also about how we study the past and use it as a guide for living in the present. The essence of history is past events reconstructed in the present to serve as provisions for life in the future. The VSTP rebellion in Semarang in 1923 is an interesting event to be reconstructed and packaged in historical learning in accordance with current developments. Learning that does not keep up with the times will only make students unable to adapt to new environments that may be present when times change. This material is important because this event is one of the important events during the movement that students must know. The aim of this research is to share knowledge information with history teachers so that they can develop learning materials that suit the needs and characteristics of students to achieve previously determined learning objectives. In this research, the researcher used a descriptive type of library research, where this method uses documents as research sources that are collected and analyzed, so that they become research data. The results that the researchers got were that VSTP was an organization of railway workers who rebelled against the railway companies during the Dutch East Indies together with ISDV because their rights as workers were not fulfilled and were looked down upon. From this incident, teachers can develop history learning materials in the form of handouts, modules, LKPD and comics packaged electronically. However, teachers are not limited to these learning materials alone, but can develop other learning materials according to students' needs and characteristics. It is hoped that the development of learning materials can help teachers in the learning process in class, and can make students more enthusiastic about learning history.